Gambaran Kesejahteraan Psikologis pada Karyawan Terdampak Pandemi COVID-19 - Umi Anugerah Izzati; Meita Santi Budiani; Olievia Prabandini Mulyana; Ni Wayan Sukmawati Puspitadewi, (Jurnal Psikologi Teori dan Terapan, 2021)
This research discusses the psychological well-being of employees affected by COVID-19 pandemic. This research was a descriptive study that used a quantitative approach. The subjects in the study were 118 employees who are working in an educational institution. Data were collected using the psychological well-being scale which was constructed based on the Ryffs (1989) concept of psychological well-being. Data analysis were carried out by compiling categorization and cross-tabulating in order to determine the psychological well-being of employees. The results showed that the psychological well-being of employees was in the high category. The dimension of psychological well-being that stands out is the life purpose, followed by the positive relationships with others.Key words: Psychological well-being, employees, COVID-19 pandemic Abstrak: Penelitian ini membahas mengenai gambaran kesejahteraan psikologis pada karyawan terdampak pandemic COVID-19. Penelitian ini merupakan penelitian deskriptif yang menggunakan pendekatan kuantitatif. Subjek dalam penelitian adalah 118 karyawan yang bekerja di salah satu institusi pendidikan. Data dikumpulkan menggunakan skala kesejahteraan psikologis yang disusun berdasarkan konsep kesejahteraan psikologis dari Ryff (1989). Analisis data dilakukan dengan menyusun kategorisasi dan melakukan tabulasi silang guna mengetahui kesejahteraan psikologis karyawan. Hasil penelitian menunjukkan kesejahteraan psikologis yang dimiliki karyawan masuk ke dalam kategori tinggi. Dimensi kesejahteraan psikologis yang menonjol adalah tujuan hidup, dilanjutkan dengan hubungan positif dengan orang lain.